Substrate evaluation for multiplication of Trichoderma spp. - Rini, C.R.; Sulochana, K.K. (Journal of Tropical Agriculture, 2008)
Cow dung, neem cake, coir pith, sorghum grains, saw dust, and rice bran, either alone or in certain combinations, with or without additives such as jaggery and wheat flour, and having differential moisture levels were evaluated as substrates for mass production of Trichoderma harzianum and T. viride. Pre-boiled sorghum grains, coir pith + neem cake (1:1), cow dung + neem cake (1:1) + wheat flour (10%) maintained high populations of T. harzianum and T. viride within 10 days of inoculation. Jaggery and wheat flour served as nutritional supplements and enhanced the conidial yield from 23.66 x 108 to 34 x 108 and 45.6 x 108 colony forming units g–1 respectively. An increase in the number of viable propagules up to 30 days was noted regardless of the substrates and its moisture levels. Although highest initial population of Trichoderma spp. was observed in sorghum grains, propagule viability was low in that compared to other substrates. Coir pith + neem cake (1:1) at 35% and 45% moisture gave longer shelf life for Trichoderma propagules.